Problems of Land Reclamation and Heat Protection of Biological Objects against Contamination by the Aviation and Rocket Launch Site - RABINSKIY, Lev N.; TUSHAVINA, Olga V. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
Hydrazine and its derivatives belong to the class of highly toxic compounds that cause the acute and chronic forms of intoxication with a predominant lesion of liver, blood system, as well as other human organs. At the same time, these products are absorbed by the ashen-gray and gray forest soils under the cation-exchange mechanism; however, the hydrazine fuels and their derivatives in moderate doses are not toxic to microorganisms and plants, and they can use the carbon and nitrogen contained in them as the sources of nutrition; herewith, high content of the products of transformation of aerospace fuel in the ashen-gray and gray forest soils is toxic to plants. To improve the biological properties of gray forest loamy soil contaminated with aerospace fuel, the sodium selenate is usually used in moderate doses that improve its enzymatic and nitrification activity, but it will not completely remove all the negative effects of pollution. As a result of exposure to hydrazine, it is necessary to develop an effective protection of biological objects and soil against the toxic effects of its highly toxic compounds.